2020
DOI: 10.1111/hsc.13114
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of age on the relationships between pre‐frailty and body measures

Abstract: This study aims to investigate the relationship between body measures and the presence of two frailty‐related phenotypes, and the moderating effect of age on this relationship. This is a secondary data analysis of the baseline data of an interventional study. The participants were residents of seven districts in Hong Kong, aged 55 or older, able to ambulate independently and to function well cognitively. Pre‐frailty refers to the presence of two frailty‐related phenotypes: low physical activity or poor handgri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…16 In recent years, the 5-item Fried frailty phenotype was one of the most commonly used indexes evaluating 22 Nevertheless, on the one hand, in previous literatures, comparing frailty and age, the superiority of predicting postoperative complications was the focus. In a retrospective analysis of 199 patients, Leung et al 23 demonstrated that age was a significant moderator of the relationship between pre-frail and body measures. Analogously, in a retrospective analysis of 8174 patients, performed by Moguilner et al, 17 the results of receiver operating characteristic curves indicated that adding age to a frailty index improved its mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…16 In recent years, the 5-item Fried frailty phenotype was one of the most commonly used indexes evaluating 22 Nevertheless, on the one hand, in previous literatures, comparing frailty and age, the superiority of predicting postoperative complications was the focus. In a retrospective analysis of 199 patients, Leung et al 23 demonstrated that age was a significant moderator of the relationship between pre-frail and body measures. Analogously, in a retrospective analysis of 8174 patients, performed by Moguilner et al, 17 the results of receiver operating characteristic curves indicated that adding age to a frailty index improved its mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, on one hand, in previous literatures, comparing frailty and age the superiority to predict postoperative complications was the focus. In a retrospective analysis of 199 patients, Leung et al [23] demonstrated that age was a signi cant moderator of the relationship between pre-frailty and body measures. Analogously, in a retrospective analysis of 8174 patients, performed by Moguilner et al [17], the results of receiver operating characteristic curve indicated that the addition of age to an frailty index could improve its mortality prediction.…”
Section: Discussionmentioning
confidence: 99%